Application of an Accessible Interface for Pharmacokinetic Modeling and In Vitro to In Vivo Extrapolation - Hines, David E.; Bell, Shannon; Chang, Xiaoqing; Mansouri, Kamel; Allen, David; Kleinstreuer, Nicole (Frontiers in Pharmacology, 2022)
Regulatory toxicology testing has traditionally relied on in vivo methods to inform decision-making. However, scientific, practical, and ethical considerations have led to increased interest in using in vitro and in silico methods to fill data gaps. While in vitro experiments have the advantage of rapid application across large chemical sets, interpretation of data from these non-animal methods can be challenging due to the mechanistic nature of many assays. In vitro to in vivo extrapolation (IVIVE) has emerged as a computational tool to facilitate this task. Specifically, IVIVE uses physiologically based pharmacokinetic (PBPK) models to estimate tissue-level chemical concentrations based on dosing parameters, then estimates the administered dose needed to achieve in vitro bioactivity concentrations within the body from these models. IVIVE results can inform metrics such as margin of exposure or prioritize potential chemicals of concern, but PBPK models have extensive data requirements. Access to input parameters and the technical requirements of applying these models has limited the use of IVIVE as a routine part of in vitro testing. As interest in using non-animal methods for regulatory and research contexts grows, our perspective is that access to computational support tools for PBPK modeling and IVIVE will be essential for broadening application and acceptance of these techniques and informing the interpretation of in vitro results. We highlight recent developments in two open-access computational support tools for PBPK modeling and IVIVE, demonstrate the types of insights these tools can provide, and discuss how these analyses may inform in vitro-based decision making.